Legal Foundation of Minors’ Rights in the Russian Federation and the Republic of Abkhazia Legal Systems - Meylis, Ekaterina Borisovna; Pozharskaya, Yuliya Vladimirovna; Prokhorova, Larisa Viktorovna; Pakhomov, Vitaliy Gavrilovich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The given article is devoted to the legal foundation of minors’ rights and freedom protection in the Russian Federation and the Republic of Abkhazia. Protection of the rights and freedoms of minors is the priority direction of legal regulation around the world. It is caused by the category of citizens which is the most vulnerable and needing in this regard protection of the state and society. Now legal systems of Russia and Abkhazia contain a number of the normative legal acts directed on regulation of this group of the public relations. The features of legal status of minors, specifics of the precepts of law directed on protection of their rights and interests and a problem of realization of separate standards of the legislation in this sphere in the presented article. The aim of research is the regulatory legal basis analysis of two countries in the indicated sphere of social relations, revealing general and particular traits of legal systems, tendencies for their further convergence, contemporary state and perspectives of family law in the sphere of minors’ rights protection analysis.
Keywords: minors’ rights; minors’ interests; parents and legal representatives’ duties; states politics in the sphere of family protection; childhood and paternity